PENGARUH PENGGUNAAN BAHASA BAKU TERHADAP SELF-ESTEEM MAHASISWA PSIKOLOGI UPI - Rahman, Syahnur; Antonietta, Johanna Rebecca; Handini, Meyta Nisa; Syarif, Dhafin Razaly (Journal of Gender Equality and Social Inclusion (gesi), 2024)
Students are agents of social change who are required to demonstrate their important and fundamental role in real life in intellectual, moral and social terms. One factor so that students can carry out their functions well is self-esteem. Self-esteem in Maslow's view is what a person feels about his own worth. Good use of standard language can increase student self-esteem and influence student self-confidence, self-quality, productivity and achievement. Therefore, this research aims to study aims to determine the effect of using standard language on students' self-esteem. Students need sufficient self-esteem to carry out their roles and functions as students properly, one of the competencies is communication skills in the form of using good and correct standard language. The research used a quantitative method done by distributing closed questionnaires to 45 random participants, and analyzed with descriptive statistic. The results of this study found that there was a positive effect from the use of standard language on the self-esteem of psychology student from Indonesia University of Education, which was marked by increased self- quality, self-confidence, productivity, and student achievement.